2004
DOI: 10.1002/ppsc.200400928
|View full text |Cite
|
Sign up to set email alerts
|

A Grand Canonical Monte Carlo Study of Adsorption and Capillary Phenomena in Nanopores of Various Morphologies and Topologies: Testing the BET and BJH Characterization Methods

Abstract: We report a Grand Canonical Monte Carlo simulation study of Ar adsorption at 77 K in silica nanopores having various morphologies/topologies. Both the morphological and topological disorders are shown to significantly affect the capillary condensation phenomenon. In the case of an ellipsoidal pore, we observe that the filling mechanism is similar to that of a cylindrical pore having the same section area but with a lower condensation pressure. We show that the adsorption/desorption hysteresis loop is asymmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
67
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 40 publications
11
67
1
Order By: Relevance
“…54,55,56,57,58,59 It can be shown with similar calculations to those described above that cavitation takes place at a pressure close to the limit of stability of the metastable liquid phase (spinodal limit). Such a nucleation process occurs at very low pressure, P d , leading to a very large hysteresis loop.…”
Section: F(r) At Constant Temperature T Is Shown Insupporting
confidence: 60%
See 1 more Smart Citation
“…54,55,56,57,58,59 It can be shown with similar calculations to those described above that cavitation takes place at a pressure close to the limit of stability of the metastable liquid phase (spinodal limit). Such a nucleation process occurs at very low pressure, P d , leading to a very large hysteresis loop.…”
Section: F(r) At Constant Temperature T Is Shown Insupporting
confidence: 60%
“…Recent simulation and theoretical results in disordered and constricted mesopores have shown that these extended defects are responsible for the nonverticality of both adsorption/desorption branches in condensation/evaporation isotherms. 24,25,26,55,56 We shall demonstrate that with the present model, the equilibrium evaporation branch is naturally located close to the pressure corresponding to hysteresis loop closure point. We tested the model by comparing its performances first with experimental data for argon measured at constant pore size but with varying temperature and second with constant temperature experimental results measured for a variety of MCM pore sizes.…”
Section: F(r)mentioning
confidence: 55%
“…These values are, by far, larger than those measured in adsorption experiments (1,9,11,40,41), reporting a wide range of S sp values from 50 to 200 m 2 =g, which depend on the initial w/c. Whereas it is wellestablished that adsorption experiments underestimate S geo sp by at least 20% (37,42), the span of experimental data depending on the adsorbate (in most cases, nitrogen at 77 K and water at 300 K) is traditionally considered the result of C-S-H structure, because contrary to water, the nitrogen accesses only part of the porosity in C-S-H (typically not the layered nanotexture of C-S-H) (43). Indeed, the Jennings colloidal model (44,45) assumes two local densities with pore features designed to justify the difference in water and N 2 measurements.…”
Section: Resultsmentioning
confidence: 99%
“…During the adsorption process, the shape is assumed to be cylindrical and the value of a is 1 (Coasne et al, 2004). The statistical thickness (t) was calculated by the Harkinse Jura model for N 2 adsorption (de Boer et al, 1963).…”
Section: Determination Of Total Porositymentioning
confidence: 99%